Cardiac computed tomography in infective endocarditis: “bridging the detection gap” - Montarello, Natalie; Bioh, Gabriel; Byrne, Calum; Hassan, Imtiaz; Androshchuk, Vitaliy; Demetrescu, Camelia; Mak, Sze Mun; Rajani, Ronak (Frontiers in Cardiovascular Medicine, 2024)
Infective Endocarditis (IE) remains a significant health challenge. Despite an increasing awareness, mortality is high and has remained largely unchanged over recent decades. Early diagnosis of IE is imperative and to assist clinicians several diagnostic criteria have been proposed. The best known are the Duke criteria. Originally published in 1994, these criteria have undergone significant modifications. This manuscript provides a timeline of the successive changes that have been made over the last 30 years. Changes which to a large degree have reflected both the evolving epidemiology of IE and the proliferation and increasing availability of advanced multi-modality imaging. Importantly, many of these changes now form part of societal guidelines for the diagnosis of IE. To provide validation for the incorporation of cardiac computed tomography (CT) in current guidelines, the manuscript demonstrates a spectrum of pictorial case studies that re-enforce the utility and growing importance of early cardiac CT in the diagnosis and treatment of suspected IE.